RESEARCH OF DESIGN PARAMETERS INFLUENCE OF BUILDING WALL, CONSTRUCTED WITH THE HELP OF 3D PRINTER, ON ITS STRESS STATE - Pahomova, Ekatarina Gennadievna; Vladislavovich, Monastyrev Pavel; Vladimirovich, Evdokimtsev Oleg; Azawi Dubla Balthazar (Journal of Applied Engineering Science, 2020)
The article presents the research results of design parameters influence of outer wall of a building erected in 3D technology, namely: wavelength of inner wall diaphragm, displacement of lower wave relative to upper wave of inner wall diaphragm (displacement of wave crest) on the stress state of a wall fragment subject to the constancy of its cross-section area. The set of data for analysis has been obtained on the basis of calculations in the SCAD ++ computer complex. The dependences of relative stresses of wall fragments on the studied factors have been obtained and the interpretation of research results has been given.